2021
DOI: 10.1101/2021.06.21.449284
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 activates ER stress and Unfolded protein response

Abstract: Coronavirus disease-2019 (COVID-19) pandemic caused by the SARS-CoV-2 coronavirus infection is a major global public health concern affecting millions of people worldwide. The scientific community has joint efforts to provide effective and rapid solutions to this disease. Knowing the molecular, transmission and clinical features of this disease is of paramount importance to develop effective therapeutic and diagnostic tools. Here, we provide evidence that SARS-CoV-2 hijacks the glycosylation biosynthetic, ER-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 125 publications
2
17
0
Order By: Relevance
“…A previous study by our group revealed an activation of the UPR pathway after 6h of SARS-CoV-2 infection 17 , corroborating previous observation of ER-stress enhancement 26 and UPR pathway activation during viral infection 18,19 . Based on these findings, we hypothesized that increased misfolded or unfolded proteins produced during SARS-CoV-2 infection may be tagged for degradation by arginylation in order to maintain cellular homeostasis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A previous study by our group revealed an activation of the UPR pathway after 6h of SARS-CoV-2 infection 17 , corroborating previous observation of ER-stress enhancement 26 and UPR pathway activation during viral infection 18,19 . Based on these findings, we hypothesized that increased misfolded or unfolded proteins produced during SARS-CoV-2 infection may be tagged for degradation by arginylation in order to maintain cellular homeostasis.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, cytoskeleton proteins were among the experimentally arginylated proteins identified in previous studies (Seo et al 56 and Wong et al 57 ). We monitored the arginylation levels of one major cytoskeleton protein, ACTB, and we observed its increase in the first 2h after infection in Calu-3 cells, with a decrease at 48h, when apoptosis-related proteins were activated 17 . The ACTB arginylation pattern was different in infected Vero cells, as was already observed for phosphorylation 89 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SQSTM1 plays a significant role in tumor transformation due to its important function as a signaling molecule interacting with many oncogenic pathways, including those involving NFE2L2/NRF2 and NFKB/NF-κB [24]. Several studies also reported evidence of mitochondrial dysfunction, excessive production of reactive oxygen species, ER stress, and unfolded protein responses in the cells infected with SARS-CoV-2 [25][26][27]. As mentioned, these pathological events could be, in part, a result of disturbed autophagy flux in the cells.…”
Section: Potential Clues and Mechanisms Supporting The Role Of Sars-cov-2 In Oncogenesismentioning
confidence: 99%
“…3) Induces ER (Endoplasmic Reticulum) Stress activated Unfolded Protein response which leads to the accelerated cell death [1600,1601,1600,1602]. 4) Protein Mutations/Deletions reported [1131,1155].…”
mentioning
confidence: 99%